2020
DOI: 10.1108/jocm-05-2019-0130
|View full text |Cite
|
Sign up to set email alerts
|

How institutional theories explain and fail to explain organizations

Abstract: PurposeThis essay raises a concern about the trajectory that new institutionalism has been following during the last decades, namely an emphasis on heterogeneity, change and agentic behavior instead of isomorphism and conformist behavior. This is a crucial issue from the perspective of the philosophy and methodology of science since a theory that admits both change and stability as a norm has less scientific weight then a theory that predicts a prevalence of passivity and isomorphism over change and strategic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 154 publications
(233 reference statements)
2
32
0
1
Order By: Relevance
“…Moreover, these change initiatives arise out of (Al-Ali et al, 2017;Boulagouas et al, 2020): (1) external pressures that influence the performance of the companies to comply and preserve the health and safety of their employees, their legitimacy and sustainability; or (2) desire to stop with old practices deemed unsatisfactory and dangerous to health and safety and develop new skills that propel safer and promising situations. Aksom and Tymchenko (2020) confirmed that these first triggers of organizational change (OC) have been evoked by the institutional theory while the normalization theory has thoroughly addressed the second ones.…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, these change initiatives arise out of (Al-Ali et al, 2017;Boulagouas et al, 2020): (1) external pressures that influence the performance of the companies to comply and preserve the health and safety of their employees, their legitimacy and sustainability; or (2) desire to stop with old practices deemed unsatisfactory and dangerous to health and safety and develop new skills that propel safer and promising situations. Aksom and Tymchenko (2020) confirmed that these first triggers of organizational change (OC) have been evoked by the institutional theory while the normalization theory has thoroughly addressed the second ones.…”
Section: Introductionmentioning
confidence: 88%
“…The institutional theory remains the dominant theory to explain organizations' relations to their environment (Suddaby et al, 2010, Aksom & Tymchenko, 2020. Institutions define social reality by the rules, a taken-for-granted social and cultural meaning system (Scott 2014, Urbano, Aparicio, & Audretsch, 2019.…”
Section: Institutions and Institutional Pressuresmentioning
confidence: 99%
“…We argue that when considering the life cycle of management fashion through the lenses of institutional theory it becomes apparent that the logic of institutional dynamics favors fashionable concepts and prevents them from deinstitutionalization. It is a master hypothesis in institutional theory which constitutes a key causal relationship (DiMaggio and Powell, 1983; Scott, 1991; Kraatz and Zajac, 1996; Aksom et al , 2020; Aksom and Tymchenko, 2020). Following the institutional line of reasoning, we would recall that in organizational fields a trend that is clearly observed at the macro level is isomorphism, that is, once organizational practice achieves such a degree of popularity that a bandwagon-like diffusion occurs, a threshold is reached when organizations begin imitate each other, and this intensive diffusion wave results in complete institutionalization when practice becomes taken-for-granted (Tolbert and Zucker, 1983; DiMaggio and Powell, 1983).…”
Section: Perceived Shortcomings In Management Fashion Literature: Dif...mentioning
confidence: 99%